The Challenges Faced by Working Mothers in Turkey: A Sociological Perspective - Zavalsız, Y. Sinan; Göksu, Gülşah (Journal of History Culture and Art Research, 2021)
This research deals with the advantages and disadvantages of the women who started to work outside the home with the Industrial Revolution in addition to the housework they were responsible for in the traditional period. With industrialization, the employment rate of women who began to work to support their family financially, gain economic independence and self-confidence, and fulfill their education requirements has increased exponentially to date. The research emphasizes that working women are stuck between their roles in working life and home. Expectations are increasing from the women who have started to take part in working life, and different roles are expected from her such as being a good wife, a good mother, a good housewife as well as being a good worker. The reflection of these expectations in families constitutes this study's main subject. The study aims to reveal how women working reflect on themselves, their children, their spouses, and their home from the working women's perspective. This study has emerged by interviewing 25 working women residing in the province of Karabuk, Turkey with a qualitative research model. The conditions such as being married and having at least one child were mandatory while assigning the research group's persons. Also, attention has been paid to ensure that the subjects included in the study work in different professions. As a result of the study, women have generally highlighted negative aspects of their work. However, the working women feel good with her contribution to home economics, has a separate economic income, and offering a better life for her children. The study shows that, despite the difficulties in working life, women who receive support from their spouses maintain a happier marriage. In contrast, those who have weak bonds with their spouses become lonely at home. At the same time, some women try to carry out this process with psychological support.